Application of social media among medical practitioner for sharing tacit knowledge: a pilot study - Amidi, Asra; Jusoh, Yusmadi Yah; Said, Mar Yah @ Mek Yah; A. Jabar, Marzanah; Abdullah, Rusli (Springer, 2017)
Tacit knowledge is perceived as the most strategically important resource of competitiveness. The rise of web-based applications such as social media also gives rise to the question on whether these applications can facilitate tacit knowledge sharing in a collaborative work environment. Previous studies have indicated that such notion is indeed possible, but there is still a lack of understanding of how social media could facilitate tacit knowledge sharing as well as the condition that is most effective in transferring this type of knowledge. Hence, it is crucial to understand the individual and technical characteristics involved in tacit knowledge sharing using social media. This research attempts to bridge this gap as there is a need to develop a holistic tacit knowledge sharing model. Towards this end, before the model is developed, the conceptual model and its instruments are validated by three field experts. A pilot study is conducted to determine the reliability and validity of the measurement indicators as well as an analysis using SPSS. The findings of the pilot study are hence presented in this paper. The results confirmed the validity of the proposed model as well as the validity and reliability of the instrument. This pilot study investigated on whether the proposed research model is viable for further research, or whether pertinent changes to the model or the methodology need to be done before the model can be used on a larger sample. Recommendations for a follow-up study concludes the paper.